O impacto do uso da metodologia ativa de aprendizagem para estudantes e professores em um curso de graduação em Administração - Maio, Edith Cristiane dos Santos (2014)
This master thesis is stimulated by reflection on teaching methods in undergraduate degree in Business Administration in a Private University of Rio de Janeiro. In a qualitative approach, the study has as its central focus the active learning method, aiming to verify the impact of the case method in the perception of students and teachers of the first period of the degree course in Business Administration, which, as methodologies for analyzing education, traditional and active, articulate in the teaching-learning process. The need for innovation in higher education, with the pursuit of teaching and learning strategies that enable students to teachers more autonomy and the role of facilitators, are the core elements that streamline the process of teaching and learning in the active method, which is premised on the approach of the authors studied. In this context, learning should be understood as knowledge construction in cooperation with students and teachers aware of their role as agents of change in the teaching process. As a teaching strategy, this paper discusses the case method, which, according to theoretical surveyed, is one of the most widespread in the area of management education.